Annexin A11 is associated with pulmonary fibrosis in African American patients with sarcoidosis - Mirsaeidi, Mehdi; Vu, Ann; Zhang, Wei; Arbieva, Zarema; Zhang, Chongxu; Abbasi, Taimur; Hakim, Anoushirvan; Schraufnagel, Dean; Sweiss, Nadera; Baughman, Robert; Garcia, Joe G.N; Machado, Roberto F (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Not available